(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2023)
This is one of the very few books written in Peranakan (mixed descent) Malay patois often referred to as Baba Malay. Once a lingua franca (Yoong and Zainab 2004, 180), Baba Malay is now a critically endangered language assessed by the Language Endangerment Index (Lee 2019, 123–124). It is estimated that there are only 1,000 speakers out of Singapore’s population of 5.61 million (Lee 2019, 127). Nala H. Lee, a linguist, discussed the predicament and documentation of Baba Malay in Singapore in her article, “Peranakans in Singapore: Responses to Language Endangerment and Documentation”. But no such work or studies have been conducted in Melaka, Malaysia, the provenance of the Southern Peranakans of the Straits Settlements from which most Singaporean Peranakans also hailed from. Regardless, I doubt that the numbers of fluent Baba Malay speakers would be any more optimistic. But original literary work in Baba Malay in the Straits Settlements is negligible.